UPAYA MENINGKATKAN KETERAMPILAN GERAK MERODA MENGGUNAKAN MEDIA PEMBELAJARAN VIDEO PADA SISWA KELAS VIIIG SMPN 2 SEMARANG - Santoso, Rias Ajis; Kresnapati, Pandu; Juwahir, Juwahir (YLPK Mahardhika, 2025)
Physical education has an important role in students' physical and mental development. One material that is often considered difficult by students is the cartwheel movement in floor exercise. This research aims to improve cartwheel movement skills in class VIII G students of SMP Negeri 2 Semarang using audio-visual learning media. This research uses the Classroom Action Research (PTK) method with two cycles. The research subjects were 32 students of class VIII G, with data collection instruments in the form of cartwheel skills tests, observations and interviews. The results showed significant improvements in students' cartwheel skills. In the pre-cycle, learning completeness only reached 40.6%, increased to 53.1% in the first cycle, and reached 78.1% in the second cycle. This increase shows that video media is effective in helping students understand and carry out cartwheels better. Thus, the use of video learning media can improve cartwheel movement skills in floor exercise at SMP Negeri 2 Semarang.